Computer-Assisted Economics - Sharpe, William F. (Journal of Financial and Quantitative Analysis, 1970)
This paper describes ways in which computers can be used to help teach elementary college economics. Most of the methods can be implemented with present-day equipment; the rest will prove feasible within a few years. Examples given here are not intended to provide a full or even a representative menu for a beginning course; they simply illustrate some of the more interesting possibilities.